Analysis of the Characterisrics of Children aged 10-12 Years and if Implication in the Development of Physical Activities and Sport - Hidayat, Yusuf; Sumpena, Asep; Hambali, Burhan (Universitas Pendidikan Indonesia (UPI), 2022)
This conceptual article describes some of the main aspects that need to be observed and considered when a physical activity and sports program will be developed and applied to children aged 10-12 years, both in the physical education setting and in sports coaching locations in schools or clubs. Sports club. The four main topics that will be described in this conceptual article are the characteristics, basis, and needs for the participation of students/athletes aged 10-12 years in sports activities, strategies for developing a conducive learning or training environment, and some practical guidelines that physical education teachers can use. or trainer to carry out the lesson or exercise.